Interfacial modulation of oil microdroplets via 1O2 stimulated by exposed Fe clusters catalyzing ozonation of 1-adamantanecaboxylic acid for destabilization - Xuan Qu; Qian Xu; Zhiqiang Chen; Ang Li (Water Research, 2026)

Which built environment factors promote urban residents' climate change adaptive behaviors? Multi-group application of an exploratory framework via adaptive motivations' mediation - Runsheng Jiang; Wei Dong; Lan Bai; Ang Qu; Yu Dong (Sustainable Cities and Society, 2026)

Fully exposed Fe clusters activated with interfacial oxygen vacancy for accelerating catalytic ozonation of electron-deficient 1-adamantanecaboxylic acid through interfacial electronic metal-support interactions - Xuan Qu; Lu Wang; Zhi-Qiang Sun; Ang Li; Jun Ma (Chemical Engineering Journal, 2025)

Predicting urban residents' climate change risk perceptions: The role of heat and green space exposure indicators in Harbin's residential environment - Runsheng Jiang; Yu Dong; Lan Bai; Wei Dong; Ang Qu (Sustainable Cities and Society, 2025)

Anti-aging effect of tea and its phytochemicals - Huijun Liang; Mei Qu; Song Ang; Dongli Li; Chengwei He (Food Research International, 2025)

Relationship between LCZ and physical activity in residential areas: A mediating role of perceptions of heat risks in climate change - Wei Dong; Runsheng Jiang; Yu Dong; Ang Qu; Yuan Yuan (Urban Climate, 2025)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Effects of Gene Alternative Splicing Events on Resistance to Cryptocaryonosis of Large Yellow Croaker (Larimichthys crocea) - Xin Li; Qiaozhen Ke; Ang Qu; Jiaying Wang; Ji Zhao; Peng Xu; Tao Zhou (Marine Biotechnology, 2024)

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Deep learning to obtain high-throughput morphological phenotypes and its genetic correlation with swimming performance in juvenile large yellow croaker - Junjia Zeng; Miaosheng Feng; Yacheng Deng; Pengxin Jiang; Yinlin Bai; Jiaying Wang; Ang Qu; Wei Liu; Zhou Jiang; Qian He; Zhijun Wang; Peng Xu (Aquaculture, 2024)

Reduced nitrogen fertilization from pre-flowering to pre-veraison alters phenolic profiles of Vitis vinifera L. Cv. Cabernet Gernischt wine of Yantai, China - Jianqiang Song; Ang Zhang; Fei Gao; Mingqing Li; Xianhua Zhao; Jie Zhang; Genjie Wang; Yuping Hou; Shiwei Cheng; Huige Qu; Shili Ruan; Jiming Li (Food Research International, 2023)

Boosting photocatalytic activity of CdLa2S4/ZnIn2S4 S-scheme heterojunctions with spatial separation of photoexcited carries - Meng Dai; Huijun Yu; Wenhan Chen; Kongyu-Ang Qu; Dong Zhai; Chengcheng Liu; Shan Zhao; Shuguang Wang; Zuoli He (Chemical Engineering Journal, 2023)

Re-Exploring the Inflammation-Related Core Genes and Modules in Cerebral Ischemia - Wenjing Lv; Junqi Jiang; Yi Xu; Zhiyuan Chen; Zixuan Wang; Ang Xing; Xueping Zheng; Tingting Qu; Qi Wan (Molecular Neurobiology, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

Dual RNA-seq reveals a host-pathogen interaction transcriptional regulation pattern between Cryptocaryon irritans and large yellow croaker (Larimichthys crocea) - Yulin Bai; Yue Liu; Ang Qu; Jiaying Wang; Ji Zhao; Qiaozhen Ke; Xintong Chen; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Aquaculture, 2023)

Identification and Expression Analysis of LncRNAs Reveal the Immune Mechanism of Visceral White-Nodules Disease Resistance in Large Yellow Croaker - Yulin Bai; Xintong Chen; Ang Qu; Yue Liu; Ji Zhao; Qiaozhen Ke; Fei Pu; Linni Wu; Hongshu Chi; Hui Gong; Tao Zhou; Peng Xu (Marine Biotechnology, 2023)

Recent Progress in Modeling and Control of Bio-Inspired Fish Robots - Boai Sun; Weikun Li; Zhangyuan Wang; Yunpeng Zhu; Qu He; Xinyan Guan; Guangmin Dai; Dehan Yuan; Ang Li; Weicheng Cui; Dixia Fan (Journal of Marine Science and Engineering, 2022)
Compared with traditional underwater vehicles, bio-inspired fish robots have the advantages of high efficiency, high maneuverability, low noise, and minor fluid disturbance. Therefore, they have gained an increasing research interest, which has led to a great deal of remarkable progress theoretically and practically in recent years. In this review, we first highlight our enhanced scientific understanding of bio-inspired propulsion and sensing underwater and then present the research progress and performance characteristics of different bio-inspired robot fish, classified by the propulsion method. Like the natural fish species they imitate, different types of bionic fish have different morphological structures and distinctive hydrodynamic properties. In addition, we select two pioneering directions about soft robotic control and multi-phase robotics. The hybrid dynamic control of soft robotic systems combines the accuracy of model-based control and the efficiency of model-free control, and is considered the proper way to optimize the classical control model with the intersection of multiple machine learning algorithms. Multi-phase robots provide a broader scope of application compared to ordinary bionic robot fish, with the ability of operating in air or on land outside the fluid. By introducing recent progress in related fields, we summarize the advantages and challenges of soft robotic control and multi-phase robotics, guiding the further development of bionic aquatic robots.

Tissue-Specific Analysis of Alternative Splicing Events and Differential Isoform Expression in Large Yellow Croaker (Larimichthys crocea) After Cryptocaryon irritans Infection - Ang Qu; Yulin Bai; Xinyi Zhang; Junjia Zeng; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Marine Biotechnology, 2022)

Characterization of a compound bioflocculant produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaeicus F6 - Lili Wang; Fang Ma; Yuanyuan Qu; Dezhi Sun; Ang Li; Jingbo Guo; Bing Yu (World Journal of Microbiology and Biotechnology, 2011)